Regenerating Potential of Dual Purpose Rapeseed (Brassica Napus L.) as Influenced by Decapitation Stress and Variable Rates of Phosphorous. Issue 4 (21st February 2023) - Imran,; Amanullah,; Al Tawaha, Abdel Rahman
ABSTRACT: The investigated study was conducted to determine the regenerating and biological potential of rapeseed and its response to different phosphorus levels and decapitation stress under water-deficit condition. These experiments were conducted at Agriculture Research Institute Mingora Swat, Pakistan, during Rabi season 2012 and 2013. Three levels of phosphorus (30, 60 and 90 kg ha −1 ) and four levels of decapitation stress from ground to the investigated levels (no stress, 10, 20 and 30 cm) were used with test crop of rapeseed having cultivar Bulbul-98. Results revealed that rapeseed crop possesses optimum regenerating potential for dual purpose and could be a prominent source of profitability. All parameters positively responded to phosphorus fertilization and decapitation stress in terms of seed and oil yield. Phosphorus @ 90 kg ha −1 increased seed yield (1170 kg ha −1 ), biological yield (11, 320 kg ha −1 ), oil yield (549.9 kg ha −1 ), thousand seed weight (3.9 g) and other yield contributing parameters followed by at par 60 kg phosphorus ha −1 . Decapitation stress influenced growth and production potential of rapeseed and produced optimum number of pods plant −1, seeds pod −1, seed yield, biological yield and oil yield on 30 cm above ground level as compared to other stress implemented plants @ of 10 and 20 cm. Based on the results it was concluded that cultivar "Bulbul-95" treated with phosphorus either @ 60 or 90 kg ha −1 should be decapitate @ 20 or either 30 cm above ground for dual purpose to use as veggies, feed and other commercial purpose and for seed production to get higher production of rapeseed under the agroclimatic condition of swat valley.